Peran Mediasi Job Satisfaction Terhadap Public Service Motivation (PSM) Dan Organizational Citizenship Behaviour (OCB) - Anna Zahroh Uswatun Chasanah; Putri Mega Desiana (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2018)
This research discusses the influence of public service motivation (PSM) and job satisfaction towards organizational citizenship behavior (OCB) in South Jakarta Municipal Administration Office. Improving public services is a priority of the government as an effort to fulfill people's wishes. The Government proclaimed bureaucratic reforms to improve the performance of the state civil apparatus. Performance of employees associated with the motivation, job satisfaction in order to provide more services to the community. This study was conducted on 108 respondents from the total population of 131 employees, with the aim to know the influence of public service motivation (PSM) and job satisfaction towards organizational citizenship behavior (OCB). The collected data is then processed using SPSS application version 22.0. The results showed that public service motivation has a direct effect on job satisfaction, as well as an effect on organizational citizenship behavior. The increasing of public service motivation (PSM) is increasing the employee's job satisfaction, and with the increase of public service motivation (PSM) also job satisfaction has an effect on improving organizational citizenship behavior (OCB), besides this research also found that public service motivation can influence directly to organizational citizenship behavior (OCB) even without mediation by job satisfaction. These results can help other organizations with similar characteristics to the South Jakarta Land Office in identifying strategies that can be done to improve organizational citizenship behavior (OCB).